2010
DOI: 10.1007/s12088-011-0098-1
|View full text |Cite
|
Sign up to set email alerts
|

Cuticle-Degrading Proteases Produced by Metarhizium anisopliae and Their Induction in Different Media

Abstract: Protease production by fourteen M. anisopliae isolates differing in geographical origin and host insect were investigated. Highest protease activity was observed during 4-8 days of culture incubation. Pr1 and Pr2 activity was investigated in various media containing different carbon and nitrogen source to evaluate the induction mechanism of these enzymes. Basal levels of Pr1 and Pr2 activity were observed in minimal medium suggesting constitutive production. Casein (1%) as an exogenous protein supplement was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Most of the strains showed high protease activity during 96~144 hr cultivation of culture which was comparable with the observations by other researchers that high protease activity was obtained at fifth day of culture in both M. anisopliae and B. bassiana [28]. Protease activity of fungal strains decreased with increase in culture age probably due to nutrient limitation or autolysis of the culture.…”
Section: Discussionsupporting
confidence: 87%
“…Most of the strains showed high protease activity during 96~144 hr cultivation of culture which was comparable with the observations by other researchers that high protease activity was obtained at fifth day of culture in both M. anisopliae and B. bassiana [28]. Protease activity of fungal strains decreased with increase in culture age probably due to nutrient limitation or autolysis of the culture.…”
Section: Discussionsupporting
confidence: 87%
“…Supakdamrongkul et al 34 reported specific lipase activity (9.41 U/mg) in purified form of lipase after four days of culture. Dhar and Kaur 35 evaluated protease activities of different isolates of B. bassiana at different days of incubation and recorded that the protease activity ranged from 0.0804 to 0.7583 U/ml at sixth day of incubation. They also reported variability in enzyme activities and found higher protease activity comparative to other fungal isolates.…”
Section: Discussionmentioning
confidence: 99%
“…The entomopathogenic fungi M. anisopliae and B. bassiana display a range of secreted enzyme activities produced as mainly secreted proteases assayed with casein as substrate or chromogenic substrates based on synthetic substrates [22,23]. Recently, transcriptomics and proteomics analysis of the exoenzymes of M. anisopliae were published [13,24,25].…”
Section: Discussionmentioning
confidence: 99%